2022
DOI: 10.1007/s10529-021-03218-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of homologous recombination events in SARS-CoV-2

Abstract: Purpose The COVID-19 disease with acute respiratory symptoms emerged in 2019. The causal agent of the disease, the SARS-CoV-2 virus, is classified into the Betacoronaviruses family. Coronaviruses (CoVs) are a huge family of viruses. Therefore, homologous recombination studies can help recognize the phylogenetic relationships among these viruses. Methods In order to detect possible recombination events in SASRS-CoV-2, the genome sequences of Betacoronaviruses were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…[4][5][6]8,46 and reported or suspected for SARS-CoV-2. 10,12,[14][15][16][17][18][19][20][21][22][23][24] SARS-CoV-2 recombinations were difficult to spot when only genetically very similar viruses were circulating, as was the case in Europe during the first epidemic episode with mutants derived from the Wuhan-Hu-1 virus. The increasing genetic diversity of SARS-CoV-2, the tremendous number of infections at global and national levels, and the unprecedented global effort of genomic sequencing (https://covariants.org/per-country), 3,25,47 raised the probability of detecting recombinants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6]8,46 and reported or suspected for SARS-CoV-2. 10,12,[14][15][16][17][18][19][20][21][22][23][24] SARS-CoV-2 recombinations were difficult to spot when only genetically very similar viruses were circulating, as was the case in Europe during the first epidemic episode with mutants derived from the Wuhan-Hu-1 virus. The increasing genetic diversity of SARS-CoV-2, the tremendous number of infections at global and national levels, and the unprecedented global effort of genomic sequencing (https://covariants.org/per-country), 3,25,47 raised the probability of detecting recombinants.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Furthermore, genetic recombinations were reported or suspected, based on the concurrent detection in consensus genomes of signature mutations of different mutants or variants. 10,12,[14][15][16][17][18][19][20][21][22][23][24] A study detected up to 1,175 (0.2%) putative recombinant genomes among 537,360 genomes and estimated that up to 5% SARS-CoV-2 having circulated in the USA and UK could be recombinants. 16 Two pandemic variants, Delta and Omicron 21K (Nextclade classification 25,26 )/BA.1 (Pangolin classification 27 ), recently succeeded each other as the predominant viruses but cocirculated for a period of several weeks, creating conditions for co-infections and subsequently recombinations.…”
Section: Text Introductionmentioning
confidence: 99%
“…In addition, 1,175 (0.2%) pu-tative recombinant genomes were identified among 537,360 genomes, and it was reported that up to 5% of SARS-CoV-2 that circulated in the USA and UK might be recombinants [18]. Moreover, the number of cases of detection of recombinant genomes is growing [10,[13][14][15][16][17][18][19][20][21][22][23][24][25]. Recently, 7 coronaviruses have been reported to be able to integrate se-quences putatively from insects [36].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding SARS-CoV-2, coinfection in the same patient with distinct variants has been reported [8][9][10][11][12][13][14]. In addition, several studies have described or suspected genetic recombinations for this virus [10,[13][14][15][16][17][18][19][20][21][22][23][24][25]. However, most of these recombinants relied solely on the coexistence of signature mutations of different SARS-CoV-2 variants in ge-nomes obtained from a single patient's sample, and they were not isolated in culture.…”
Section: Introductionmentioning
confidence: 99%
“…Such genetic recombinations are extremely frequent for viruses of family Coronaviridae , and they have already been identified for endemic human coronaviruses (Lai, 1996; Zhang et al, 2015; So et al, 2019; Gribble et al, 2020). Regarding SARS-CoV-2, the occurrence of recombinations has been reported or suspected (Yi, 2019; Yeh and Contreras, 2020; Haddad et al, 2021; Ignatieva et al, 2021; Jackson et al, 2021; Taghizadeh et al, 2021; Varabyou et al, 2021; Kreier, 2022; Wertheim et al, 2022; He et al, 2022; Sekizuka et al, 2022; Colson et al, 2022b; Lacek et al, 2022; Lohrasbi-Nejad, 2022; Bolze et al, 2022; Ou et al, 2022; Belen Pisano et al, 2022; Burel et al, 2022). Very recently, we described the identification and culture of two SARS-CoV-2 recombinants, one between the B.1.160 and Alpha/20I variants in a patient chronically-infected with SARS-CoV-2 (Burel et al, 2022), and another between the Delta/21J AY.4 and Omicron 21K/BA.1 variants in patients infected approximately 10 weeks after the start of the period of co-detection of these two variants in our geographical area (Colson et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%